Pengaruh Terhadap Keputusan Konsumen Berkunjung Ke Pemandian Air Panas Simpang Balik Kabupaten Bener Meriah - MSM, Zainuddin; Teniro, Alwin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2025)
The purpose of this study is to determine the influence of products and location on consumers' decisions to visit Simpang Balik Hot Springs in Bener Meriah Regency. The benefit of this research is to improve insights and skills in the field of marketing management. This research also aims to develop a mindset to improve abilities and expand the scientific treasures with a sample of 75 people. The results of the study show that, partially, from the results of the discussion, a regression equation can be formed, namely Y = 1.591 + 0.367 + 0.289. From the results of the partial hypothesis test, the product and location had a significant effect on consumer decisions at the hot springs of Bener Meriah Regency. The relationship between independent and dependent variables is strong, and the ability of the product and location to influence consumer decisions is 0.512